MENJADI GURU PROFESIONAL (ISU DAN TANTANGAN MASA DEPAN) - Arifin, Zaenal (Prodi Teknologi Pendidikan, 2014)
Abstract, Teaching it is an art because every teacher has their own style and characteristics. Therefore, every teacher has different styles and techniques in teaching. So is their performance, models, they ways they deliver the material, the use of methods and media as well as evaluation. In teaching, teachers are expected to not get stuck with the routine of traditional teaching (teacher-centered), which assumes that the learner is an